Direito à saúde para a população trans: uma análise sobre a universalização do acesso para pessoas trans ao ambulatório de sexualidade do Hospital Universitário da UFMA, entre 2016 e 2020 - ARAUJO, Bruna Barbosa (2023)
This research aimed to analyze how the LGBTI+ population has accessed their right to health in the context of advancing conservatism and with drawal of legal rights,based on the experience of the sexuality outpatient clinic of the Hospital Universitarioda UFMA (HUUFMA) from 2016 to 2020, standing on the principles of Universalityand Integrality of the Sistema Unico de Saude (SUS). This is an exploratory study with a qualitative basis, which used Dialectical and Historical Materialismas its methodo fanalysis, seeking to describe the research object in its multiple determinationsandconsidering the process of overthrowing public policies as a phenomenoninsertedinthe complex and contradictory advance of the conservatism in Brazil. Asemi-structured interview was applied with four professionals from the multidisciplinary team and ten transgender people attended by thesexualit youtpatient clinic of the hospital from December 2022 to June 2023. Thequestionsofthe interview included their dynamics of life, socioeconomic profile andthemainbarriers and challenges to access healthcare in the public systemas atransgenderperson. The collected data was analyzed and interpreted by detailingandsystematizing the narratives. The results point to the impacts generatedbytheadvance of conservatism in Brazil, especially from 2016 onwards, whichdirectlyimpacted the implementation of the Sexuality Outpatient Clinic of the HUUFMAandthe access to body-changing surgeries and hormone therapy. Weaknesseswerefound in the structure of the Sistema Unico de Saude, such as the lack of fundingandthe privatization caused by the neoliberal recession system. This scenariomakesitdifficult for transgender people to find in the public health systemthe support neededfor a safe gender transition, contradicting the principles of Universality andIntegralityof the SUS.